Organizacja i właściwość wojskowych sądow admiralskich i marynarskich w latach 1920–1939 - Skelnik, Julian M. (Studia Iuridica Toruniensia, 2010)
<!--[if gte mso 9]> <![endif]--> When Poland regained sovereignty in November 1918 there was created new judiciary. Depending on the region, in the very beginning, courtsmartial were acting on the base of German, or Austro-Hungarian procedural martial law. This was changed in the May 1920, when Austro-Hungarian procedural martial law was introduced on the territory of the whole country. This law distinguished army court-martial, navy courts-martial, and common Highest Court-Martial. Due to diff erent organizations from years 1920, 1923, 1924, and 1929 lower navy courts-martial, called Sea- man Courts-Martial, had their residences in Puck, Toruń, Modlin, Brześć nad Bugiem, and Warszawa. Higher courts-martial, called Admiral Courts- Martial, had their residences in Grudziądz, Warszawa, and Brześć nad Bugiem. In 1937 new procedural martial law was introduced in Poland, but still it was based on Austro-Hungarian model. Due to new organization, since 1937 every lower court-martial could act as a Seaman Court-Martial, and correspondingly every higher court-martial could act as an Admiral Court-Martial. Additionally in 1938 there was created single Seaman Court-Martial in Gdynia. Jurisdiction of Polish navy courts-martial varied within years. At some time not only navy seaman and off icers, but also civil staff of the ship, where subject to military law. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->